A high-resolution radio continuum study of the dwarf irregular galaxy IC 10 - Westcott, J; Brinks, E; Beswick, R; Heesen, V; Argo, M; Baldi, R; Fenech, D; McHardy, I; Smith, D; Williams, D (Oxford University Press, 2017)
We present high-resolution e-Multi-Element Radio Linked Interferometer Network radio continuum maps of the dwarf irregular galaxy IC 10 at 1.5 and 5 GHz. We detect 11 compact sources at 1.5 GHz, five of which have complementary detections at 5 GHz. We classify three extended sources as compact HII regions within IC 10, five sources as contaminating background galaxies and identify three sources that require additional observations to classify. We do not expect that any of these three sources are supernova remnants as they will likely be resolved out at the assumed distance of IC 10 (0.7 Mpc). We correct integrated flux densities of IC 10 from the literature for contamination by unrelated background sources and obtain updated flux density measurements of 354±11 mJy at 1.5 GHz and 199 ± 9 mJy at 4.85 GHz. The background contamination does not contribute significantly to the overall radio emission from IC 10, so previous analysis concerning its integrated radio properties remains valid.